(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Thyroid carcinoma is typically indolent and has a favorable prognosis when compared to other types of cancer. In advanced stages of thyroid cancer, distant metastases are typically appearing in the lungs, bones, and lymph nodes. Thyroid cancer breast metastasis is extremely rare. A case of follicular variant of papillary thyroid carcinoma (FVPTC) has been reported in this context, which was manifested as low FDG avid soft tissue density lesions in breast in a whole body PET-CT scan 4 years after thyroidectomy for papillary thyroid carcinoma (PTC) in a 46-year-old woman. The lesions were suspected as metastatic, which were confirmed through histopathology. Bangladesh J. Nuclear Med. 28(1): 156-158, 2025